Ultrasonographic Evaluation of the Effect of Patient Position on Size of Subclavian Vein: An Observational, Prospective Study - Poudel, Deepak; Pyakurel, Kumud; Pokhrel, Anuja; Jha, Anant Piyush; Khanal, Kanak; Adhikari, Milan (Birat Journal of Health Sciences, 2024)
Introduction: The use of real time ultrasound guided cannulation of the subclavian vein is increasing in critically ill and surgical patient population. The larger diameter of the veinduringcannulationhelps to reduce the frequency of associated complications. Objectives: To compare change in the diameter of the subclavian vein in 15° head down and 15° head up position with that of the supine position. Methodology: A prospective observational study was conducted among the patients visiting Department of Anesthesia and Critical Care in Birat Medical College Teaching Hospital for elective surgery from April 2023 to January 2024. Results: The diameter of subclavian vein increased by 18.38±9.1% in head down (Trendelenburg) position and decreased by 15.8±9.8 % in head up position compared to supine position when evaluated by real time ultrasound. Conclusion: The head down (Trendelenburg) increases the diameter of the subclavian vein, so this position is advisable during cannulation or any other procedures.